Metode Emo-Demo Merupakan Metode Efektif Dalam Perubahan Perilaku Pencegahan Dalam Pernikahan Dini Pada Remaja Putri - Dwi Purwanti; Suparji Suparji; Heru Santoso Wahito Nugroho (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Early marriages are marriages conducted by 18 years old, who physically, physiologically and psychologically are not yet prepared to take on the responsibilities of marriage, if they are done, it can disturb reproductive health This study aims to develop a health promotion model using Emo-Demo through the Theory of Planned Behavior approach to the prevention of early childhood marriage behavior in young girls. This research is a quantitative research using a quasi-experimental design, namely research that aims to reveal a causal relationship by involving a control group in addition to the experimental group (7). In this design, the experimental group was given treatment and the control group was not. In both treatment groups, it was started with a pre-test and after giving the treatment, another measurement was held (post-test). This research was conducted in the KB Village, Jambe Wangi Village, Sempu District, Banyuwangi Regency. The population was all young women who were in the KB Village of Jambe Wangi Village, Sempu District, Banyuwangi Regency, totaling 60 people. The sample in this study was young women with a sample size of the control group 30 people, and treatment group 30 people. The sampling technique used simple random sampling. The research variables were Attitude toward the behavior, Subjective norms, Perceived behavior control, Behavioral Intention, Action to prevent early marriage. The data were analyzed descriptively to determine the frequency distribution which included the frequency and percentage of the aspects being measured. Furthermore, data analysis used the Kolmogorov-Smirnov homogeneity test, the Wilcoxon Signed Ranks Test and the Mann-Whitney Test with α